2013
DOI: 10.1002/jssc.201201067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different sample pre‐treatments for multi‐residue analysis of organochlorine and pyrethroid pesticides in chrysanthemum by gas chromatography with electron capture detection

Abstract: The widespread use of insecticides in Chinese herbal medicines has created a compelling need for the development of a multiresidue analytical method to help assure herbs safety. The operating variables affecting the performance of the multiresidue analysis of 34 organochlorine and 12 pyrethroid pesticides in chrysanthemum, a widely used kind of Chinese herbal medicines, were evaluated. Three different extraction solvents including n-hexane and its mixtures with acetone and petroleum ether were compared, and n-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Liquid-liquid extraction (Guo et al, 2010;Pizzutti et al, 2007), low-temperature precipitation (Li et al, 2007;Su et al, 2011), gel permeation chromatography (Fernandez Moreno, Arrebola Lieanas, Garrido Frenich, & Martinez Vidal, 2006;Xue et al, 2013), and treatment with sulfuric acid (Xue, Hao, & Peng, 2008) are traditional cleanup approaches for the removal of complex co-extractives. To reduce the consumption of organic solvents and achieve simple operation, QuEChERS-based methods have attracted much attention for the analysis of targets in oily and CHM commodities (Chen et al, 2012;Guan et al, 2013;Koesukwiwat, Ehotay, Mastovska, Dorweiler, & Leepipatpiboon, 2010) and showed good efficiency.…”
Section: Introductionmentioning
confidence: 98%
“…Liquid-liquid extraction (Guo et al, 2010;Pizzutti et al, 2007), low-temperature precipitation (Li et al, 2007;Su et al, 2011), gel permeation chromatography (Fernandez Moreno, Arrebola Lieanas, Garrido Frenich, & Martinez Vidal, 2006;Xue et al, 2013), and treatment with sulfuric acid (Xue, Hao, & Peng, 2008) are traditional cleanup approaches for the removal of complex co-extractives. To reduce the consumption of organic solvents and achieve simple operation, QuEChERS-based methods have attracted much attention for the analysis of targets in oily and CHM commodities (Chen et al, 2012;Guan et al, 2013;Koesukwiwat, Ehotay, Mastovska, Dorweiler, & Leepipatpiboon, 2010) and showed good efficiency.…”
Section: Introductionmentioning
confidence: 98%
“…This proposed method was superior in the levels of LODs, LOQs and EFs, implying it could achieve much higher sensitivity and enrichment compared with other reported techniques. As a microextraction approach, ME-VADLLME has fulfilled environmental considerations by only using a total organic solvent amount of 5.05 mL per sample, whereas 20-90 mL of organic solvent is typically required by most of other methods [3,5,7,8,34,[45][46][47]. Without the need to endure lengthy and time-consuming procedures taking more than 30 min for SPE, MSPD, GPC solvent evaporation, or SPME analyte equilibration [3,[6][7][8]34,[44][45][46][47], the combination method based on dispersive analyte transfer is able to perform simultaneous extraction/preconcentration rapidly within 15 min, and allows high sample throughput in routine screening exercise.…”
Section: Comparison Of the Proposed Methods With Conventional Quechersmentioning
confidence: 99%
“…Chrysanthemum is known as a complex matrix comprising of pigments, alkaloids, flavonoids, sterols, and essential oils, etc. To remove the potential co-extractives that may interfere with the determination of the analytes of interest, isolation of pesticides from chrysanthemum needs complicated cleanup procedures, involving gel permeation chromatography (GPC) and solid phase extraction (SPE) [8]. These procedures usually require large amounts of solvents and are time-consuming, and also presented relatively high limits of detection (LODs).…”
Section: Introductionmentioning
confidence: 99%
“…Detection of pesticide residues in fruit, vegetable, and tobacco with GC with electron capture detection (ECD), GC–MS/MS and LC–MS/MS has been reported in many studies . However, the samples which were injected into GC or LC usually contain components harmful to the equipment and affect the analysis results.…”
Section: Introductionmentioning
confidence: 99%